Korupsi dan Akbiatnya: Perspektif Ekonomi Islam - Nur Kholis (Millah: Journal of Religious Studies, 2006)
This article explains the problem of corruption in general and its negative impact to society, politics, economy, and bureaucracy from Islamic economic viewpoint This article finds that corruption is a complex phenomenon. It is the outcome of the inter action between social, cultural, economic, and political factors. It cripples all aspects of social life. Corruption makes society disintegrated, politics chaotic, economy sluggish nonproductive and bureaucracy inefficient The Qur'an and The Sunnah as the primary sources of Islamic economic provide rich vocabularies, teachings and con text forbid and harm corruption. Corruption is forbidden and Allah SWT does not love corruption and has threatened the corruptible with a heavy punishment